A 3D ray-tracing based model for radiowave simulations in vegetated environments with wind-induced dynamics - Leonor, Nuno; Fernandes, Telmo R.; Sánchez, Manuel García; Caldeirinha, Rafael F. S. (Frontiers in Antennas and Propagation, 2025)
IntroductionThis paper proposes an extension of a ray-tracing based model for radiowave propagation in the presence of vegetation, to account for the wind-induced channel dynamics in vegetated environments. The original propagation model uses various point scatterers with specific re-radiation and it has been proven to be suitable for a wide range of scenarios. However, the swaying motion of the tree branches and leaves, as an effect of the wind, creates a constantly changing environment that influences the propagating radio signals in both amplitude and phase, resulting in signal level fluctuations.MethodsA large measurement campaign intending to record and characterize the effect of wind-induced dynamics in vegetated environments, was conducted in a controlled environment, inside an anechoic chamber. Experiments included various wind directions and at varying speeds: stationary (0 m/s), low (1.9 m/s) and high (4.7 m/s). The dynamic re-radiation pattern of trees present in the radio path were recorded at 20 and 62.4 GHz signal frequencies. The available experimental data was then used to develop a statistical model which is sought to characterize wind-induced dynamics of the point scatterers’ re-radiation function. Finally, the performance of the proposed dynamic model while predicting the received signal level fluctuations inside a tree formation scenario, was assessed against dynamic directional spectra measurements conducted in a controlled environment, for four different artificially generated wind incidences and two wind speeds, low (1.9 m/s) and high (4.7 m/s).Results and discussionThis experiment proved that the proposed elementary model could be an asset on the characterization of the time-varying effects found in vegetation areas under wind influence.